2015
DOI: 10.1186/s12940-015-0077-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between perfluoroalkyl acids and kidney function in a cross-sectional study of adolescents

Abstract: BackgroundPerfluoroalkyl acids are synthetic compounds widely used in industrial and commercial applications. Laboratory studies suggest that these persistent and bioaccumulative chemicals produce oxidant stress and damage glomerular endothelial cells, raising concern regarding the impact of these compounds on renal function.MethodsWe performed cross-sectional analyses of data 1960 participants aged 12–19 years of the 2003–2010 National Health and Nutrition Examination Surveys. PFAA exposure was assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 51 publications
(60 reference statements)
6
73
0
Order By: Relevance
“…13 In adolescents, PFOA and PFOS have been found to be significantly associated with dyslipidemia. 14 PFOS and PFNA concentrations have also been shown to be associated with lower levels of insulin growth factor-1 (IGF-1) in children and, 15 among 12–19 year olds in NHANES 2003–2010, those with the highest quartile of serum PFC had significantly lower renal glomerular function compared to those in the lowest quartile, 16 although the possibility of reverse causation cannot be excluded in this cross-sectional study.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…13 In adolescents, PFOA and PFOS have been found to be significantly associated with dyslipidemia. 14 PFOS and PFNA concentrations have also been shown to be associated with lower levels of insulin growth factor-1 (IGF-1) in children and, 15 among 12–19 year olds in NHANES 2003–2010, those with the highest quartile of serum PFC had significantly lower renal glomerular function compared to those in the lowest quartile, 16 although the possibility of reverse causation cannot be excluded in this cross-sectional study.…”
Section: Introductionmentioning
confidence: 69%
“…28 Furthermore, PFASs have been associated with increases in serum uric acid in children ages 12–19 years enrolled in NHANES, and have been linked to reduced kidney function in children. 16 In addition, it has been reported that PFOS and PFNA concentrations were associated with lower levels of IGF-1 in children, 15 which, in turn, have been associated with metabolic syndrome 29 and increased risk of cardiovascular events in later life. 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study used a dipstick to measure proteinuria (Factor-Litvak et al, 1999). Among the studies that examined estimated glomerular filtration rate (eGFR), seven studies used creatinine based estimating equations (Fadrowski et al, 2010, Farzan et al, 2016, Garcia-Esquinas et al, 2013, Kataria et al, 2015a, Kooijman et al, 2015, Loghman-Adham, 1998, Watkins et al, 2013). Four studies used Cystatin C based estimating equations to determine eGFR (Fadrowski et al, 2010, Skroder et al, 2015, Hawkesworth et al, 2013, Filler et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…These include studies of fluoride levels(Xiong et al, 2007; Liu et al, 2005), aflatoxin (Hassan et al, 2006a) and ochratoxin (Hassan et al, 2006b), maternal smoking levels (Taal et al, 2011, Kooijman et al, 2015), secondhand smoking (Garcia-Esquinas et al, 2013), Bisphenol A, Triclosan, Benzophenone-3 (Trasande et al, 2013), PFOA (Geiger et al, 2013; Watkins et al, 2013; Kataria et al, 2015a), Bisphenol-A-glycidyl-dimethacrylate (bisGMA) (Trachtenberg et al, 2014), melamine exposure (Lam et al, 2008; Guan et al, 2009), polycyclic aromatic hydrocarbons (PAHs) (Farzan et al, 2016) and various phthalate compounds (Trasande et al, 2014, Tsai et al, 2016) (Table 3). The study designs included 12 cross-sectional, 1 case control, 2 prospective cohort, 1 retrospective cohort, and 1 randomized clinical trial.…”
Section: Resultsmentioning
confidence: 99%